Scale and change: Assaf Gavron's CrocAttack!, Nathan Englander's 'Sister Hills' and Elia Suleiman's Divine Intervention. Issue 1 (2nd January 2018) - Willems, Brian
ABSTRACT: The concept of scale is becoming lodged within contemporary theories about reality, change and possibility. This assumption materialises as an increased interest in diverse forms of otherness on the one hand, and an almost fanatic insistence on the non-identity of objects on the other (Franco Moretti, Thomas Piketty, Graham Harman). Scale thus functions both as a medium through which difference can be understood and the absolute limit to which human reason can stretch, and never beyond. Works based on the Israeli–Palestinian conflict have a long history of grappling with the paradox of scale. Assaf Gavron's novel CrocAttack! (2006) depicts diverse forms of otherness in a missed point of understanding between an Israeli and a Palestinian. Nathan Englander's short story 'Sister Hills' (2012) highlights the limits of scale in characters which take the 'as if' of Jewish law at its word. The structure of this paradox of scale is read through Marshall McLuhan and Graham Harman in order to show how being confronted with the non-identity of scale actually encourages adaptation or change to take place. The metaphor developed from this reading is that of 'the wall', which is used in an interpretation of Palestinian director Elia Suleiman's Divine Interventions (2002).